Vachellia sieberiana var. woodii, a high-altitude encroacher: the effect of fire, frost, simulated grazing and altitude in north-western KwaZulu-Natal, South Africa. Issue 4 (13th December 2019) - Russell, Jennifer M; Tedder, Michelle J; Demmer, Stuart
Abstract : Savannas and grasslands throughout the world are experiencing bush encroachment, which has serious consequences for net primary productivity. In South Africa, Vachellia sieberiana is encroaching into the savannas and high-altitude grasslands of KwaZulu-Natal. We investigated the role of fire, frost and simulated grazing (mowing of the grass sward) on the establishment of transplanted V. sieberiana saplings (as change in stem diameter) along an altitudinal gradient in north-western KwaZulu-Natal using analysis of variance. Altitude had a significant effect on sapling size. There was no response to treatments at the high-altitude site. At the mid-altitude site, sapling stem diameter decreased in response to fire treatment and increased in response to mowing. At the low-altitude site, there was a negative response to frost and a positive response to fire and to mowing. At both the mid- and low-altitude sites there was a positive response when fire and mowing were combined. None of the treatments were able to prevent the establishment of V. sieberiana . Rangeland managers need to maintain a tree:grass ratio that provides the best production of forage. Fire is frequently used to control bush encroachment, but, with V. sieberiana being well adapted to survive fire, managers will need to devise other methods to conserve important grassy biomes.